The Battle for Libya : killings, disappearances and torture (Amnesty International LondonGB, 2011)
Covers developments tu to late July 2011 when the conflict was tightly contested between al-Gaddafi and opposition forces; largely based on an Amnesty International fact-finding visit to Libya between 26 February and 28 May 2011. Also draws on information collected by Amnesty's fact-finding visits between 20 April and 12 and 20 June to Tunisia.
Keywords: POLITICAL CONFLICTS